From Faith to Fintech: The Role of Religiosity within the UTAUT Framework in Shaping Islamic Digital Banking Adoption - Ibnu Muttaqin; Umarul Faruq; Agep Rumanto (Jurnal Sistem Informasi Bisnis, 2026)
The rapid growth of digital banking services has revolutionized the global financial industry. However, the adoption of Islamic digital banking continues to warrant empirical examination, particularly in Muslim-majority countries such as Indonesia. As religious values increasingly influence financial decision-making, it is important to understand the behavioral factors that drive the adoption of Islamic digital banking services. This study aims to examine the determinants of Islamic digital banking adoption in Indonesia by employing the Unified Theory of Acceptance and Use of Technology (UTAUT), extended by incorporating religiosity as both a direct predictor and a moderating variable. A total of 223 respondents who are active users of Islamic digital banking services participated in this study. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that social influence and facilitating conditions significantly affect both behavioral intention and actual usage behavior. Religiosity also plays a direct role in shaping customers’ behavior, but it does not moderate the relationship between behavioral intention and actual usage. In contrast, perceived usefulness and perceived ease of use do not show a significant effect on adoption intention. These findings highlight the importance of leveraging community-based social influence and strengthening digital infrastructure. Islamic banks are therefore encouraged to collaborate with credible influencers, enhance service reliability, and integrate Islamic values into customer education programs in order to promote wider adoption of Islamic digital banking services.